2021
DOI: 10.3390/nu13093167
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Associations of Dietary Energy Density and Energy Intake, Macronutrients with Obesity in Patients with Type 2 Diabetes (JDDM 63)

Abstract: To investigate the association between dietary energy density (DED) and obesity in people with type 2 diabetes mellitus. Moreover, we compared the strength of the associations of DED with intake of energy and macronutrients in terms of obesity as well as nutritional factors that have long been used for medical nutritional therapy. Cross-sectionally investigated were 1615 outpatients with type 2 diabetes who attended 26 clinics nationwide with diabetes specialists. Odds ratios (ORs) were calculated for the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although DED is defined as the energy density of a total diet, there is no consensus about the appropriate method of ED calculation. The studies that excluded beverages from DED calculation mentioned that beverages intake is highly variable and DED calculation based on inclusion of beverages might diminish its association with health outcomes [ 22 ]. However, beverages are an important part of usual dietary intakes and excluding them is not logical scientifically.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DED is defined as the energy density of a total diet, there is no consensus about the appropriate method of ED calculation. The studies that excluded beverages from DED calculation mentioned that beverages intake is highly variable and DED calculation based on inclusion of beverages might diminish its association with health outcomes [ 22 ]. However, beverages are an important part of usual dietary intakes and excluding them is not logical scientifically.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with inconsistent results evaluated the association between DED and health outcomes. While one study reported the effects of diets with high DED in increasing adiposity and weight gain among patients with diabetes [ 22 ], several other studies did not show any association between DED and obesity or BMI in general population [ 18 , 29 , 30 ]. Similarly, for the association between DED and metabolic disorders, several studies revealed the positive association between diets with high DED and odds of MetS in adults [ 26 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the energy intake in the non-obese group was comparable to that in the obese group. The obese group consumed more high-energy foods than the non-obese groups, although in small volumes (i.e., high energy density [ 33 ]), such as meat/processed meat, sweets, and sugar-sweetened beverages. Conversely, the non-obese group consumed more low-energy-dense foods such as vegetables, fruits, seaweed, fish/seafood, and soybeans/soy products.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that dietary energy density, the consumption of processed food, red meat intake, and other dietary factors were associated with the prevalence of obesity, cardiovascular diseases, type 2 diabetes, etc. [13][14][15].…”
Section: Introductionmentioning
confidence: 99%